2023
DOI: 10.1021/acs.chemrestox.2c00354
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry Analysis of DNA and Protein Adducts as Biomarkers in Human Exposure to Cigarette Smoking: Acrolein as an Example

Abstract: Acrolein is a major component in cigarette smoke and a product of endogenous lipid peroxidation. It is difficult to distinguish human exposure to acrolein from exogenous sources versus endogenous causes, as components in cigarette smoke can stimulate lipid peroxidation in vivo. Therefore, analysis of acrolein-induced DNA and protein adducts by the highly accurate, sensitive, and specific mass spectrometry-based methods is vital to estimate the degree of damage by this IARC Group 2A carcinogen. This Perspective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 129 publications
0
14
0
Order By: Relevance
“…Acrolein can induce oxidative DNA damage due to ROS homeostasis disorders and free radical generation. Moreover, this aldehyde readily reacts with deoxyguanosine (dG), producing two exocyclic DNA adducts, α- and γ-hydroxy-1, N2-propano-2′-deoxyguanosine (a-HOPdG and c-HOPdG), but is also capable of forming adducts of 2′-deoxyadenosine and 2′-deoxycytidine DNA bases and thymidine [ 108 , 160 , 161 ]. The result of the formation of acrolein-DNA adducts is mutations within DNA fragments crucial to the fate of the cell.…”
Section: Acrolein In the Development Of Lung And Oral Cancermentioning
confidence: 99%
“…Acrolein can induce oxidative DNA damage due to ROS homeostasis disorders and free radical generation. Moreover, this aldehyde readily reacts with deoxyguanosine (dG), producing two exocyclic DNA adducts, α- and γ-hydroxy-1, N2-propano-2′-deoxyguanosine (a-HOPdG and c-HOPdG), but is also capable of forming adducts of 2′-deoxyadenosine and 2′-deoxycytidine DNA bases and thymidine [ 108 , 160 , 161 ]. The result of the formation of acrolein-DNA adducts is mutations within DNA fragments crucial to the fate of the cell.…”
Section: Acrolein In the Development Of Lung And Oral Cancermentioning
confidence: 99%
“…Acrolein can also form protein adducts, specifically targeting lysine and cysteine. , Cai et al investigated reactions of acrolein with proteins and peptides; they concluded that cysteine was the most reactive amino acid and that the initial products reacted further with protein amino groups . Reaction of acrolein with Cys-34 of albumin by Michael addition was reported by Columbo et al and others; reactions with lysine and histidine were also observed. Reactions of acrolein with hemoglobin and albumin have recently been reviewed . Protein adducts of acrolein can also be generated during lipid peroxidation .…”
Section: Discussionmentioning
confidence: 99%
“…The effect of acrolein on the key signaling pathways for cell proliferation/death is also significant for the pathogenesis of many diseases [ 9 , 10 ]. Many studies indicate that the mutagenic properties of acrolein result from its significant effectiveness in its direct interaction with DNA and the formation of adducts, primarily with deoxyguanosine [ 11 , 12 ]. In addition, this aldehyde, while interacting with DNA, simultaneously weakens or completely disables repair mechanisms [ 13 ].…”
Section: Introductionmentioning
confidence: 99%